Uwarunkowania rozwoju polityki społecznej II Rzeczypospolitej Polskiej w świetle ustawodawstwa międzynarodowego i konstytucji marcowej - Grabowska, Jolanta (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The aim of this study was to determine the impact of the March Constitution and international legislation, that is the Treaty of Versailles and conventions of the International Labour Organisation ILO, on the emergence and development of social policy of the reviving of Polish state in the interwar period.To better understand the intentions contained in those acts, in the initial part of the study the situation prevailing in Poland after the First World War was briefly described and the immediate needs of the Polish society resulting therefrom. In the following part of the work the provisions of various legal acts, whose regulations influenced the direction of social development of the Polish state in the interwar period, starting from the Treaty of Versailles through ILO Conventions ratified by Poland to the March Constitution, were described.After analyzing the content of legal acts mentioned above it was concluded that the regulations contained in the provisions were essential foundations of the reviving social policy in the Second Republic of Poland.
Keywords: polityka społeczna; usługi socjalne; Międzynarodowa Organizacja Pracy; Konstytucja marcowa Polski; Traktat wersalski (1919)